Tari Woleka: Seni Ritual Magis Masyarakat Marapu Di Sumba Barat - S. Hudijono (Institut Seni Indonesia Denpasar, 2009)
This article aim to to study art of ritual magical which leave from social context of society culture of West Sumba which is is important to be [done/conducted] to see artistic attachment of ritual with his society. This dance have vitally function, especially for society which still embrace trust of Marapu. The function related to importance of ritual, where that related/relevant ritus is also named by party of woleka. Ritus it is a ceremony form to have an out, to blessing and of subsistence/livelihood to ancestor late.